Three-atom co-doped reed biochar as well as preparation method and application thereof
By using phosphorus, nitrogen and sulfur three-atom co-doping technology in reed biochar, combined with hydrothermal carbonization and microwave-assisted pyrolysis technology, biochar is prepared to efficiently remove tetracycline TC in water, solving the problem of inefficient removal in the prior art.
Patent Information
- Application Number
- CN202510036437.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is inefficient in removing tetracycline TC in water, and the development process of multi-atom doped carbon materials is complex and expensive, and lacks a systematic introduction.
Reed biochar with rich pore structure and high adsorption capacity was prepared by combining hydrothermal carbonization with microwave-assisted pyrolysis technology.
It significantly improves the adsorption capacity of biochar and can efficiently remove tetracycline TC in water, with a removal rate of 95%.
Smart Images

Figure CN119841314A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water pollution treatment and biochar preparation, and in particular to a three-atom co-doped reed biochar, a preparation method and an application thereof. Background Art
[0002] In recent years, only 10% to 20% of tetracycline TC is absorbed by humans or animals during use, and most of it continues to accumulate in the environment, eventually directly or indirectly affecting human health. Therefore, effective measures must be taken to treat tetracycline accumulated in water to reduce its potential threat. At present, the adsorption method in the physical method is widely used because of its advantages such as simple operation, wide application, low cost and high treatment efficiency. It is also considered to be one of the methods with broad application prospects for removing tetracycline from water.
[0003] Biochar is a solid material produced by the pyrolysis of biomass under anoxic or anaerobic atmosphere. It has a unique pore structure and has become a research hotspot in the field of adsorbents. However, the adsorption capacity of biochar is limited, and it usually needs to be treated to improve its adsorption performance. Heteroatom doping technology can change the polarity of the material by changing the skeleton structure and electronic configuration of biochar materials, thereby further improving its adsorption capacity. The main atoms currently used for doping are boron, nitrogen, phosphorus, sulfur, etc. The heteroatom-doped carbon materials used to adsorb pollutants in water are mainly concentrated in nitrogen doping, sulfur doping, or single-atom doping such as boron doping. The co-doping research of other atoms is very limited. This is mainly because there are many forms of heteroatom doping, and the lack of directional theoretical guidance during co-doping leads to a complex and expensive development process. There is currently no process for systematic introduction of multi-atom doping processes.
[0004] Biochar is usually prepared by hydrothermal carbonization or electric heating such as tube furnace or muffle furnace. In recent years, microwave-assisted pyrolysis technology has been widely selected as a biochar pyrolysis instrument due to its advantages of fast heating speed, low energy consumption and high energy utilization. However, there is no systematic research on the selection of pyrolysis methods and the combined use of pyrolysis instruments during pyrolysis. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a reed biochar co-doped with phosphorus, nitrogen and sulfur atoms, a preparation method and an application thereof. The present invention has easy-to-obtain raw materials, simple operation, mild conditions, low operating environmental pollution, and less energy loss, and provides a clean and efficient method for the preparation of modified biochar. The prepared modified biochar can efficiently remove TC in water.
[0006] To achieve the above object, the present invention provides the following technical solutions.
[0007] In a first aspect, the present invention provides a method for preparing tri-atom co-doped reed biochar, comprising the following steps:
[0008] (1) crushing reed straw into powder;
[0009] (2) After soaking the straw powder in a mixed solution consisting of a phosphorus source, a nitrogen source and a sulfur source, transferring it to a high-temperature reactor for heating and keeping it warm for a period of time, and then filtering and drying it to obtain a biochar precursor; the phosphorus source is phosphoric acid with a concentration of 5-15 mol / L;
[0010] (3) mixing the biochar precursor and the microwave absorbent in a crucible, placing the mixture in a microwave pyrolysis furnace, sealing the instrument and connecting it to a protective gas, and keeping the mixture at a certain pyrolysis temperature for a period of time to obtain a biochar sample;
[0011] (4) The biochar sample is washed until the pH of the filtrate is neutral, and finally dried to obtain the tri-atom co-doped reed biochar.
[0012] In the present invention, in step (1), the reed straw is crushed and then passed through a sieve of 60 to 100 meshes.
[0013] In the present invention, in step (2), the nitrogen source is selected from one or more of melamine, urea or ammonium carbonate; the sulfur source is selected from one or more of diphenyl disulfide, sodium thiosulfate or thiourea.
[0014] In the present invention, in step (2), the impregnation ratio of the reed straw powder to the phosphoric acid solution is 1:50 to 3:50 g / mL; the mass ratio of the reed straw powder to the nitrogen source and the sulfur source is 1:(1-3):(1-3).
[0015] In the present invention, in step (2), the phosphoric acid concentration is 8-12 mol / L.
[0016] In the present invention, in step (2), the heating temperature is 140-180° C. and the insulation time is 8-12 h.
[0017] In the present invention, in step (3), the microwave absorber is columnar activated carbon; the mass ratio of the microwave absorber to the biochar precursor is 1:1 to 4:1. For biomass materials, adding microwave absorbers will enhance the microwave absorption performance of the material, increase the heating rate, facilitate the carbonization of the material and the formation of pores inside the material, and then affect its adsorption capacity through pore filling.
[0018] In the present invention, in step (3), the protective gas is carbon dioxide; the pyrolysis power of the microwave pyrolysis furnace is set to 600-1600W, the pyrolysis temperature is 400-600°C, and the insulation time is 1.5-3h.
[0019] In the present invention, in step (4), the biochar sample is washed with deionized water; the purpose of washing is to wash the prepared material to neutrality, otherwise the acidity is too high and will affect its adsorption effect. The electrostatic effect in a strong acid environment will inhibit adsorption.
[0020] In the present invention, in step (2) and step (4), drying is carried out in an oven at a drying temperature of 100-110°C.
[0021] In a second aspect, the present invention also provides a three-atom co-doped reed biochar prepared by the above preparation method.
[0022] In a third aspect, the present invention provides an application of the above-mentioned three-atom co-doped reed biochar in removing tetracycline TC from water.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention combines hydrothermal carbonization with microwave-assisted pyrolysis technology to prepare tri-atom co-doped reed biochar. The phosphorus source enriches the pore structure inside the material, while the nitrogen source and sulfur source provide more effective sites for adsorption. The tri-atom co-doping greatly improves the adsorption capacity of the material. In terms of application scope, tri-atom co-doped reed biochar can efficiently and massively remove tetracycline TC from polluted water. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron microscope image of the three-atom co-doped reed biochar material prepared in Example 1.
[0026] Figure 2 Nitrogen adsorption-desorption curve and pore size distribution diagram of the three-atom co-doped reed biochar material prepared in Example 1.
[0027] Figure 3 The TC removal effect of the biochar material prepared in this example.
[0028] Figure 4 This is the fitting result of the isothermal adsorption model of the three-atom co-doped reed biochar material prepared in Example 1.
[0029] Figure 5 This is the fitting result of the adsorption kinetic model of the three-atom co-doped reed biochar material prepared in Example 1.
[0030] Figure 6 This is a scanning electron microscope image of the biochar material prepared in Comparative Example 1.
[0031] Figure 7 This is a scanning electron microscope image of the biochar material prepared in Comparative Example 2.
[0032] Figure 8 The TC removal effect of the biochar materials prepared in Comparative Examples 1-6. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0035] The materials and instruments used in the following examples are all commercially available, and the raw materials are of analytical grade. In the following examples, unless otherwise specified, the data obtained are the average values of more than three repeated tests.
[0036] The technical solutions and technical effects provided by the present application are described in detail below through more specific embodiments.
[0037] Example 1
[0038] This embodiment provides a method for preparing three-atom co-doped reed biochar, which specifically includes the following steps:
[0039] Crush the reed straw until it passes through a 60-100 mesh sieve, take 4g of straw powder, 8g of urea and 8g of sodium thiosulfate in a 250mL beaker, and add 100mL of 10mol / L phosphoric acid solution to mix thoroughly. Pour the mixed solution into a high-temperature reactor and heat it at 160℃ for 10h. After heating, filter the solution to obtain a biochar precursor, and put it into an oven at 110℃ to dry the water. Take the dried biochar precursor in a corundum crucible, add columnar activated carbon in a ratio of 1:3 between the weight ratio of biochar precursor and microwave absorber, and send it into a microwave pyrolysis furnace, set the pyrolysis temperature to 500℃, the pyrolysis power to 800W, and keep it at 500℃ for two hours. After it cooled to room temperature, the columnar activated carbon was taken out, and the pyrolyzed biochar sample was repeatedly rinsed with deionized water. After the pH of the filtrate was neutral, it was placed in an oven at 110°C, dried, and ground through a 200-500 mesh sieve to obtain three-atom co-doped reed biochar, which was labeled MBC500-800 W.
[0040] Figure 1 This is a SEM image of the three-atom co-doped reed biochar prepared in Example 1. Figure 1It can be seen that the surface of the three-atom co-doped reed biochar prepared in Example 1 of the present application is rough and contains a lot of debris. The presence of debris can provide more effective sites for adsorption and improve its adsorption performance.
[0041] The elemental composition of the three-atom co-doped reed biochar prepared in Example 1 is shown in Table 1:
[0042] Table 1
[0043] Material C O P S N MBC500-800W 58% 17% 13% 7% 4%
[0044] It can be seen from Table 1 that the three atoms were successfully doped into the biochar surface, and the C element content in the biochar was the highest. By comparing the doped three-atom content, it can be seen that the P doping content was the highest.
[0045] The specific surface area (measured by 3Flex America Micromeritics analyzer) and pore structure of the three-atom co-doped reed biochar prepared in Example 1 are shown in Table 2 and Figure 2 As shown:
[0046] Table 2
[0047] Material <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Total pore volume (cm 3 / g)]]> Average pore size (nm) MBC500-800W 1217 1.23 4.05
[0048] Depend on Figure 2 It can be seen that the material shows type I and type IV isotherms, indicating that there are microporous and mesoporous structures inside the material. When the p / p0 of the material is very small, the rapid increase in the adsorption of N2 indicates that there is a microporous structure inside the material. As p / p0 increases, the overlap between the adsorption and analytical curves decreases, which also indicates that there is a mesoporous structure inside the material. The pore size distribution of the material is mainly in the range of 1-5nm.
[0049] From Table 2, we can see that the specific surface area of MBC500-800 W can reach 1217m 2 / g, which is related to its internal micropore and mesoporous structure. The large specific surface area and rich pore structure can provide sufficient adsorption sites and larger contact area for the adsorption process.
[0050] Example 2
[0051] The only difference from Example 1 is that the amount of urea added is 12 g, and the other step parameters are the same as those in Example 1; a three-atom co-doped biochar material is obtained, which is marked as MBC500-800W-12N.
[0052] Example 3
[0053] The only difference from Example 1 is that the ratio of microwave absorber to biochar precursor is 2:1, and the other step parameters are the same as those in Example 1; a three-atom co-doped biochar material is obtained, which is marked as MBC500-800W-2:1.
[0054] Example 4
[0055] The only difference from Example 1 is that the microwave pyrolysis temperature is 400° C., and the other step parameters are the same as those in Example 1; a three-atom co-doped biochar material is obtained, which is marked as MBC400-800W.
[0056] Example 5
[0057] The only difference from Example 1 is that the microwave pyrolysis temperature is 600° C., and the other step parameters are the same as those in Example 1; a three-atom co-doped biochar material is obtained, which is marked as MBC600-800W.
[0058] Application performance testing
[0059] 1. Testing the adsorption capacity of the biochar materials obtained in Examples 1-5 for tetracycline TC
[0060] Specifically, it includes: first, prepare a tetracycline TC solution with a concentration of 60 mg / L, and take 100 mL and transfer it to a conical flask. Then weigh 0.15 g / L of biochar material and add it to the conical flask solution. Next, place the conical flask in a magnetic stirring device, set a certain speed (400r / min) and temperature (25°C), and take samples at 0, 5, 15, 25, 40, and 60 within 1 hour. After filtering the water sample through a 0.22μm nylon organic phase filter membrane, add it to a 2mL injection bottle. The residual concentration of TC was tested using a high-performance liquid chromatograph model LC-20A to determine the difference in adsorption performance of each material. Set the characteristic wavelength channel of 365nm to detect TC, and select acetonitrile and a mixture of ultrapure water and formic acid (1000:1) as two mobile phases.
[0061] The adsorption performance of biochar materials is evaluated by the adsorption rate w, and the formula is as follows:
[0062]
[0063] Where C and C0 are the concentrations of TC solution before and after adsorption (mg / L), V is the volume of TC solution (L), and m represents the amount of biochar used (g).
[0064] Figure 3 The figure is a diagram showing the effect of using the biochar material prepared in Examples 1-5 of the present invention to remove TC from water. Figure 3 It can be seen that the removal rate of TC in water by the biochar material MBC500-800 W prepared in Example 1 is 95%; the removal rate of TC in water by the carbon material MBC500-800W-12N prepared in Example 2 is 85%; Figure 3It can be seen that the material MBC500-800W-2:1 prepared in Example 3 has a TC removal rate of 90% in water; the carbon material MBC400-800W prepared in Example 4 has a TC removal rate of 86% in water; and the carbon material MBC600-800W prepared in Example 5 has a TC removal rate of 91% in water.
[0065] 2. Verification of the performance of the three-atom co-doped reed biochar prepared in Example 1 in removing TC from water
[0066] 1) Performance verification of three-atom co-doped reed biochar in removing different concentrations of TC
[0067] 100 mL of TC solutions with concentrations of 80, 100, 120, 150, and 200 mg / L were prepared in a conical flask, and the amount of adsorbent MBC500-800 W prepared in Example 1 added was 0.15 g / L. The removal results of TC by MBC500-800 W in TC solutions of different concentrations are shown in Table 3:
[0068] Table 3
[0069]
[0070]
[0071] From the results in Table 3, it can be seen that with the increase of TC solution concentration, the adsorption capacity of three-atom co-doped reed biochar MBC500-800 W has increased significantly. When the TC solution concentration is 200 mg / L, the maximum adsorption capacity of MBC500-800 W for TC is 400.3 mg / g. The high adsorption capacity indicates that when MBC500-800 W is used to treat pollutants in actual water bodies, a lot of treatment costs can be saved.
[0072] The experimental data in Table 3 were fitted with the isothermal adsorption model Langmuir model and Freundlich model to obtain the adsorption isotherm model fitting curve of MBC500-800 W for TC in water. The fitting results are shown in Figure 4 And as shown in Table 4.
[0073] Table 4
[0074]
[0075] Correlation coefficient R of MBC500-800 W material fitting Langmuir model fitting 2The correlation coefficient is higher than that of the Freundlich model, so the Langmuir model can better describe the adsorption behavior of MBC500, which is a monolayer adsorption. The value of the factor n in the Freundlich model is greater than 1, indicating a good adsorption process.
[0076] 2) Verification of the performance of three-atom co-doped reed biochar in removing TC at different times
[0077] 100mL of 50mg / L TC solution was placed in a conical flask, and the amount of adsorbent MBC500-800 W added was 0.15g / L. Within 1 hour, samples were taken at 0, 5, 15, 25, 40, and 60min. The removal results of TC by MBC500-800 W at different times are shown in Table 5:
[0078] Table 5
[0079] time Adsorption capacity (mg / g) 5 110 15 147 25 169 40 181 60 190
[0080] The experimental data in Table 5 were fitted with the pseudo-first-order kinetic model and the pseudo-second-order kinetic model to obtain the adsorption kinetic fitting curve of MBC500-800 W for TC in water. The fitting results are shown in Figure 5 and as shown in Table 6.
[0081] The MBC500-800 W material has a higher degree of fit with the quasi-secondary dynamic model, and the correlation coefficient R 2 Both can reach 0.99, which is higher than the correlation coefficient of the pseudo-first-order kinetic model. Therefore, the pseudo-second-order kinetic model can more accurately describe the adsorption process of TC by the material. The adsorption process of the pseudo-second-order adsorption kinetic model can be divided into two steps. First, the carbon material adsorbs TC on its surface. When the adsorption is close to saturation, chemical adsorption is carried out. The adsorption constant k value is less than 1, which proves that the carbon material adsorbs TC faster.
[0082] Table 6
[0083]
[0084] Comparative Example 1
[0085] The only difference from Example 1 is that phosphoric acid, sulfur source and nitrogen source are not added, and the remaining step parameters are the same as those in Example 1; undoped reed straw biochar material is obtained, which is marked as BC500.
[0086] SEM image of the undoped reed straw biochar material BC500 prepared in Comparative Example 1. Figure 6 It can be seen that BC500 presents a tube bundle structure, and the pore structure appearing in its cross section is arranged in an orderly honeycomb shape. The pores and their internal structure can provide more adsorption sites for the adsorption process.
[0087] The specific surface area and pore structure of the undoped reed straw biochar material BC500 prepared in Comparative Example 1 are shown in Table 7:
[0088] Table 7
[0089] Material <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Total pore volume (cm 3 / g)]]> Average pore size (nm) BC500 11.4 0.03 11.2
[0090] As shown in Table 7, the specific surface area of the undoped reed straw biochar material BC500 is relatively small, only 11.4 m 2 / g, its internal pore structure is relatively simple, and the average pore size is about 10nm, which proves that the interior of the material is mainly mesoporous structure.
[0091] The effect of the biochar material prepared in this comparative example was verified, and the results showed that the adsorption rate of tetracycline in water by the unadulterated reed straw biochar material BC500 prepared in this comparative example was 5%.
[0092] Comparative Example 2
[0093] The only difference from Example 1 is that after the biochar precursor is obtained by the high-temperature reactor, it is transferred to a tubular furnace and heat treated at a heating rate of 10°C / min. The remaining step parameters are the same as those in Example 1, and the three-atom doped biochar prepared in the tubular furnace is obtained, which is marked as GBC500.
[0094] Comparative Example 2 SEM image of the tri-atom doped biochar material GBC500 prepared by a tube furnace. Figure 7 It can be seen that the morphology and structure of GBC500 are similar to that of MBC500-800 W prepared in Example 1, and a lot of debris appears on the surface.
[0095] Comparative Example 2 The specific surface area and pore structure of the three-atom doped biochar material GBC500 prepared by a tube furnace are shown in Table 8:
[0096] Table 8
[0097] Material <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Total pore volume (cm 3 / g)]]> Average pore size (nm) GBC500 978 0.85 3.48
[0098] From Table 8, we can see that the specific surface area of GBC500 can reach 978m 2 / g, but compared with the MBC500-800 W prepared in Example 1, the specific surface area is smaller, which is attributed to the difference in the working principles of the two carbon-making equipment. The tubular furnace is a conventional electric heating device, which realizes the pyrolysis of biomass by converting electrical energy into thermal energy, and the heat source enters the inside of the material from the outside of the material, while the microwave pyrolysis furnace realizes the heating of biomass by converting electromagnetic energy into thermal energy, and the heat source is transferred from the inside of the material to the outside of the material, and the carbonization inside the material is more complete, and the pore structure is more developed. Therefore, the three-atom doped biochar MBC500-800 W obtained by microwave pyrolysis in Example 1 has a larger specific surface area and a better pore structure.
[0099] The biochar material prepared in this comparative example was tested for its application performance. The results showed that the adsorption rate of tetracycline in water by the tri-atom doped biochar material GBC500 prepared by a tubular furnace in this comparative example was 80%.
[0100] Comparative Example 3
[0101] The only difference from Example 1 is that no sulfur source and nitrogen source are added, and the remaining step parameters are the same as those in Example 1; a phosphorus-doped reed straw biochar material is obtained, which is marked as PBC500.
[0102] In Comparative Example 3, no sulfur source and nitrogen source were added, and the specific surface area and pore structure of the phosphorus-doped reed straw biochar material PBC500 were obtained as shown in Table 9:
[0103] Table 9
[0104] Material <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Total pore volume (cm 3 / g)]]> Average pore size (nm) PBC500 550 1.1 7.81
[0105] As shown in Table 9, the specific surface area of phosphorus-doped reed straw biochar material PBC500 is 550 m 2 / g, while the average pore size is relatively large, and the interior of the material is mainly a mesoporous structure.
[0106] The biochar material prepared in this comparative example was tested for its application performance. The results showed that the adsorption rate of tetracycline in water by the phosphorus-doped reed straw biochar material PBC500 prepared in this comparative example was 71%.
[0107] Comparative Example 4
[0108] The only difference from Example 1 is that no phosphorus source is added, and water is used instead, and the other step parameters are the same as those in Example 1; sulfur and nitrogen co-doped reed straw biochar material is obtained, which is marked as WBC500.
[0109] Comparative Example 4: No phosphorus source was added, and the specific surface area and pore structure of sulfur-nitrogen co-doped reed straw biochar material WBC500 were obtained as shown in Table 10:
[0110] Table 10
[0111] Material <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Total pore volume (cm 3 / g)]]> Average pore size (nm) WBC500 288 0.17 2.3
[0112] As shown in Table 10, the specific surface area of sulfur-nitrogen co-doped reed straw biochar material WBC500 is 288 m 2 / g, which is smaller than the effect of phosphorus-doped and phosphorus-nitrogen co-doped biochar.
[0113] The biochar material prepared in this comparative example was subjected to an application performance test, and the results showed that the adsorption rate of tetracycline in water by the sulfur-nitrogen co-doped reed straw biochar material WBC500 prepared in this comparative example was 35%.
[0114] Comparative Example 5
[0115] The only difference from Example 1 is that phosphoric acid is replaced with 10 mol / L hydrochloric acid, and the other step parameters are the same as those in Example 1; sulfur and nitrogen co-doped reed straw biochar material is obtained, which is marked as LBC500.
[0116] In Comparative Example 5, no phosphorus source was added, and the specific surface area and pore structure of the hydrochloric acid-modified sulfur-nitrogen co-doped reed straw biochar material LBC500 were obtained as shown in Table 11:
[0117] Table 11
[0118] Material <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Total pore volume (cm 3 / g)]]> Average pore size (nm) LBC500 820 0.96 4.7
[0119] As shown in Table 11, the specific surface area of the hydrochloric acid modified sulfur and nitrogen co-doped reed straw biochar material LBC500 is 820 m 2 / g, and its contribution to the pore structure of biochar is much lower than that of the material prepared in Example 1.
[0120] The biochar material prepared in this comparative example was tested for its application performance. The results showed that the adsorption rate of tetracycline in water by the hydrochloric acid-modified sulfur-nitrogen co-doped reed straw biochar material LBC500 prepared in this comparative example was 75%.
[0121] Comparative Example 6
[0122] The only difference from Example 1 is that the material obtained in this comparative example is commercially available activated carbon; marked as commercially available. The biochar material prepared in this comparative example was tested for application performance, and the results showed that the commercially available activated carbon purchased in this comparative example had an adsorption rate of 41% for tetracycline in water.
[0123] The present invention also verifies on the basis of Example 1 that reed straw is replaced with other biomass materials (that is, the only difference from Example 1 is that reed straw is replaced with other biomass materials, and the other steps and parameters are the same as Example 1), such as corn straw, bagasse, etc. The results show that under the same adsorbent dosage, TC concentration and adsorption time conditions, the removal effect of TC by the prepared three-atom co-doped corn straw biochar is 82%, while the removal effect of TC by the prepared three-atom co-doped bagasse biochar is 78%, and its adsorption effect on TC is much lower than that of the three-atom co-doped reed straw biochar prepared in Example 1. The reason for this difference can be attributed to the differences in the content of cellulose, lignin and hemicellulose in different biomasses. This difference affects the formation of the pore structure of the three-atom co-doped biochar, thereby affecting its adsorption performance.
[0124] Based on the above examples and comparative examples, it can be seen that the three-atom co-doped reed biochar MBC500-800W provided in the examples of the present application has better physical and chemical properties, and its specific surface area can reach 1217m 2 / g, the material has rich micropores and mesoporous structures inside, and the debris on the surface can also provide more effective sites for adsorption. MBC500-800W can effectively remove TC in water. When the dosage is 0.15g / L and the TC concentration is 100mL 60mg / L, the removal effect of TC can reach 95% within 1h; its adsorption kinetic model has a higher degree of fit with the quasi-second-order kinetic model, and the adsorption isotherm model has a higher degree of fit with the Langmuir model, and the maximum adsorption capacity can reach 744.40mg / g.
[0125] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing three-atom co-doped reed biochar, characterized in that: The following steps are involved: (1) crushing reed straw into powder; (2) After soaking the straw powder in a mixed solution consisting of a phosphorus source, a nitrogen source and a sulfur source, transferring the mixture to a high-temperature reactor for heating and keeping the mixture warm for a period of time, filtering and drying the mixture to obtain a biochar precursor; the phosphorus source is phosphoric acid with a concentration of 5-15 mol / L; (3) After mixing the biochar precursor and the microwave absorbent in a crucible, the mixture is placed in a microwave pyrolysis furnace, the instrument is sealed and connected with a protective gas, and the mixture is kept at a certain pyrolysis temperature for a period of time to obtain a biochar sample; (4) The biochar sample is washed until the pH of the filtrate is neutral, and finally dried to obtain the tri-atom co-doped reed biochar.
2. The preparation method according to claim 1, characterized in that: In step (1), the reed straw is crushed and passed through a 60-100 mesh sieve.
3. The preparation method according to claim 1, characterized in that In step (2), the nitrogen source is selected from one or more of melamine, urea or ammonium carbonate; the sulfur source is selected from one or more of diphenyl disulfide, sodium thiosulfate or thiourea; and the phosphorus source is phosphoric acid with a concentration between 8-12 mol / L.
4. The preparation method according to claim 1, characterized in that In step (2), the impregnation ratio of the reed straw powder to the phosphoric acid solution is 1:50-3:50 g / mL; and the mass ratio of the reed straw powder to the nitrogen source and the sulfur source is 1:(1-3):(1-3).
5. The preparation method according to claim 1, characterized in that In step (2), the heating temperature is 140-180°C and the insulation time is 8-12 h.
6. The preparation method according to claim 1, characterized in that: In step (3), the microwave absorber is columnar activated carbon; and the mass ratio of the microwave absorber to the biochar precursor is 1:1 to 4:
1.
7. The preparation method according to claim 1, characterized in that In step (3), the protective gas is carbon dioxide, the pyrolysis power of the microwave pyrolysis furnace is set to 600-1200 W, the pyrolysis temperature is 400-600° C., and the insulation time is 1.5-3 h.
8. The preparation method according to claim 1, characterized in that: In step (4), the biochar sample is washed with deionized water.
9. A three-atom co-doped reed biochar prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the three-atom co-doped reed biochar according to claim 9 in removing tetracycline TC from water.